Analysis Of The Impact Of The Covid-19 Pandemic On Financial Performance And Survival Of Companies In The Food Beverage Idustrial Sector And Restaurant Services From Potential Bankruptcy Using Financial Ratio And Taffler Analysis Models - Akbar, Nur Ardi Fahmi; Lestari, Etty Puji; Budiyanti, Hety (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This study aims to identify the influence analysis of the Covid-19 pandemic's impact on financial performance and company resilience from potential bankruptcy in the food and beverage sector and restaurant service sector listed on The Indonesia Stock Exchange (IDX) before and during the COVID-19 pandemic. This study was measured using rentability ratios, profitability ratios, liquidity ratios, solvency ratios, and Taffler Models to measure the potential for bankruptcy of a company. The results indicated significant differences in the rentability ratios represented by the return on assets ratio in companies in the food and beverage sector. Meanwhile, other ratios and potential bankruptcy using the Taffler model did not show a significant difference. Furthermore, in restaurant service companies, there were significant differences in all ratios tested, namely rentability ratio, profitability ratios, liquidity ratios, solvency ratios, and bankruptcy potential using the Taffler model. This study also shows that the average company in the food and beverage sector has resistance to potential bankruptcy compared to those in the restaurant service sector.